Push vs pull production strategy: case study in the coffee production industry - Xavier, Matilde de Sousa Leitão Gomes (2020)
In a globalization environment and where uncertainty is more present, it is necessary to adapt supply chains, in order to allow companies to be able to ensure their competitive advantage. In this way, Portuguese COMPANY X feels the need to understand the advantages associated with a change in its production strategy. Considering the lean strategies that help in this adaptation and that can be applied throughout the supply chain, this study focuses specifically on the implementation of one of these strategies in the production area. Among all the existing businesses in the company, it was challenged that this analysis should focus on the coffee business, since it is a growing business. Therefore, this study focuses on the analysis of a possible implementation of a production pull strategy, in order to assess whether the impacts on production costs and on holding stock costs are advantageous compared to those existing in the current production strategy - push production strategy. At the same time, it is intended to compare the effects caused by different demand variation scenarios between the current production strategy and the strategy under analysis. To analyze if there would be advantages in implementing a pull strategy in the production area, a simulation tool was used - Anylogic. In this tool, was made a model which represent the production process and another one that represents the stock process.